PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN JALAN TOL PEKANBARU–PADANG (SEKSI PEKANBARU–BANGKINANG) DI DESA BUKIT KRATAI - Silitonga, Wendi; ", Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Pekanbaru-Padang toll road (Section of Pekanbaru-Bangkinang) is the government's effort to facilitate regional traffic and improve the distribution of goods and services to support economic growth. –Bangkinang) In Bukit Kratai Village, 2) Knowing what influences people's perception of the Pekanbaru– Padang toll road construction (Section Pekanbaru –Bangkinang) In Bukit Kratai Village the method used in this research is descriptive quantitative method. The results obtained are: 1). Community perception of toll road construction is positive with aspects of location (100%), development activities (60.2%), development impact (60.2%), development benefits (100%). 2) Factors that influence people's perceptions of toll road construction are Knowledge (Education and Objectives of toll road construction) Experience (House Distance, Status in the Community and Expectations) Keywords: Perception, Society, Quantitative, Pekanbaru- Bangkinang Toll Road construction